Intermediate algebra - Miller, Julie 1962- (McGraw-Hill Higher Education, 2007)
Intermediate Algebra offers a refreshing approach to the traditional content of the course. Presented in worktext format, Intermediate Algebra offers a review of problem solving, solving equations in two and three variables, a chapter devoted to functions, polynomials, radicals and complex numbers, factoring and quadratic functions, rational expressions, and inequalities. Other topics include exponential and logarithmic functions and conic sections.